Optimized CeO2 Nanowires with Rich Surface Oxygen Vacancies Enable Fast Li‐Ion Conduction in Composite Polymer Electrolytes. Issue 1 (9th March 2022) - Gao, Lu; Wu, Nan; Deng, Nanping; Li, Zhenchao; Li, Jianxin; Che, Yong; Cheng, Bowen; Kang, Weimin; Liu, Ruiping; Li, Yutao
Abstract : Low‐cost and flexible solid polymer electrolytes are promising in all‐solid‐state Li‐metal batteries with high energy density and safety. However, both the low room‐temperature ionic conductivities and the small Li + transference number of these electrolytes significantly increase the internal resistance and overpotential of the battery. Here, we introduce Gd‐doped CeO2 nanowires with large surface area and rich surface oxygen vacancies to the polymer electrolyte to increase the interaction between Gd‐doped CeO2 nanowires and polymer electrolytes, which promotes the Li‐salt dissociation and increases the concentration of mobile Li ions in the composite polymer electrolytes. The optimized composite polymer electrolyte has a high Li‐ion conductivity of 5 × 10 −4  S cm −1 at 30 °C and a large Li + transference number of 0.47. Moreover, the composite polymer electrolytes have excellent compatibility with the metallic lithium anode and high‐voltage LiNi0.8 Mn0.1 Co0.1 O2 (NMC) cathode, providing the stable cycling of all‐solid‐state batteries at high current densities. Abstract : Low‐cost Gd 3+ ‐doped CeO2 nanowires with large surface area and rich surface oxygen vacancies were prepared by the electrostatic blowing firstly, and then, PEO‐based electrolyte was prepared by introducing the as‐obtained nanowires. The cells with optimized composite polymer electrolyte exhibit a stable cycling performance with an improved current density up to 1.2 mA cm −2 . This represents a staggering, threefold increase in the current density window over the current state‐of‐the‐art polymer–electrolyte‐based batteries.